2014
DOI: 10.5296/rae.v6i3.5354
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Validity of Wagner’s Law in the OECD Economies

Abstract: In this study, the validity of Wagner's Law, which explains the relationship between public expenditures and economic growth, has been analyzed over its alternative models by using the data from 27 OECD economies between the years 1995-2012. It has been carried out by utilizing unit root, co-integration and error correction tests panel data analyses, the long term co-efficiencies between public expenditures and economic growth. In order to test the relationship of co-integration, the Pedroni, Johansen-Fisher a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…The result shows that economic growth is a major factor influencing government expenditure in Nigeria. This finding is in conformity with most empirical evidence in the literature (Bayrak and Esen, 2014;Akinlo, 2013;Olomola, 2004). In contrast, the effect of the negative component of GDP (economic downturn) on government expenditure is negatively significant and larger in magnitude, with a 1% decrease in government expenditure resulting in about 3.83% decrease in government expenditure.…”
Section: Empirical Results and Discussionsupporting
confidence: 92%
“…The result shows that economic growth is a major factor influencing government expenditure in Nigeria. This finding is in conformity with most empirical evidence in the literature (Bayrak and Esen, 2014;Akinlo, 2013;Olomola, 2004). In contrast, the effect of the negative component of GDP (economic downturn) on government expenditure is negatively significant and larger in magnitude, with a 1% decrease in government expenditure resulting in about 3.83% decrease in government expenditure.…”
Section: Empirical Results and Discussionsupporting
confidence: 92%
“…The Keynesian hypothesis is rejected in the long and short-term for both real and nominal variables. Bayrak et al (2014) analyse the validity of the Wagner's law in 27 OECD countries between 1995 and 2012. The authors use the unit-root co-integration and error correction tests on a panel data.…”
Section: The Wagner's Law Testing: State Of the Artmentioning
confidence: 99%
“…The empirical evidence from this literature is however mixed and controversial across countries, data, model specifications and econometric techniques. While some studies (Ram, 1987;Ahsan et al, 1996;Cotsomitis et al, 1996;Thornton, 1999;Islam, 2001;Al-Faris, 2002;Chang, 2002;Aregbeyen, 2006;Srinivasan, 2013;Bayrak and Esen, 2014) found support for Wagner's Law, other studies (Ansari et al, 1997;Biswal et al, 1999;Ghali, 1999;Burney, 2002;Huang, 2006) reported results contradicting Wagner's law. Some other studies (Singh & Sahni, 1984;Ahsan et al, 1992;Afxentiou & Serletis, 1996;Sinha, 1998;Bagdigen & Cetintas, 2004;Dogan & Tang, 2006) showed no evidence for both propositions.…”
Section: Introductionmentioning
confidence: 99%